2008
DOI: 10.1291/hypres.31.83
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Abdominal Fat Accumulation and Insulin Resistance in Hemodialysis Patients

Abstract: It is well known that obesity and insulin resistance are closely related to the development of type 2 diabetes.However, the exact pathogenic mechanism underlying the insulin resistance in renal disease has not been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
(25 reference statements)
3
26
0
Order By: Relevance
“…In our results, we showed that the abdominal adiposity, either measured by WC or Ci, did not correlate with IR indices after multivariable adjustments (table 3). Two small-scale studies [20,21] also demonstrated similar results as ours; that is, abdominal adiposity was not an optimal indicator of IR in dialysis population. We commonly used WC as the measure of abdominal adiposity in the general population; however, WC represented both visceral adipose tissue and subcutaneous adipose tissue and the distinguished adipose tissue corresponded to different outcome results [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…In our results, we showed that the abdominal adiposity, either measured by WC or Ci, did not correlate with IR indices after multivariable adjustments (table 3). Two small-scale studies [20,21] also demonstrated similar results as ours; that is, abdominal adiposity was not an optimal indicator of IR in dialysis population. We commonly used WC as the measure of abdominal adiposity in the general population; however, WC represented both visceral adipose tissue and subcutaneous adipose tissue and the distinguished adipose tissue corresponded to different outcome results [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, persons with potential significant fluid overload were excluded from this study, and bioimpedance was performed after a dialysis session when patients had reached their dry weight. Furthermore, because of limitations associated with the use of bioimpedance analysis for assessing body fat mass, the differentiation between subcutaneous and metabolically active visceral fat could not be assessed in the present study (25). Finally, insulin resistance is a consequence of high energy intake in nondiabetic hemodialysis patients, but it was not possible to infer that the increase in HOMA-IR was causally related to an adverse CV outcome in a 12-wk intervention.…”
Section: Discussionmentioning
confidence: 90%
“…The incidence of cardiovascular disease is high even in non-obese individuals with a BMI within the normal range who have an accumulation of visceral fat. 21 Recently, VFA has been significantly associated with insulin resistance 22 and with the prevalence of CVD in participants from the Framingham Heart Study; 23 thus, the accurate assessment of both body fat distribution and VFA is critical for assessing the risk of arteriosclerotic disease. Ohkawa et al 24 reported that VFA in hemodialysis patients increased irrespective of BMI, and a positive relationship existed between VFA and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%